Research on the deep peak-shaving cost allocation mechanism considering the responsibility of the load side - Yang, Zhao; Yibo, Wang; Chuang, Liu; Guowei, Cai; Weichun, Ge; Yueyang, Xu; Ziwei, Xiang (Frontiers in Energy Research, 2023)
Under the goal of carbon reduction, China has carried out a series of institutional reforms and innovations on renewable energy consumption.However, the existing allocation rules for peak-shaving cost concentrate on the power side only. In the context of high energy penetration rates, peak-shaving cost significantly increase, and the economic pressure on the power side sharply increases. As the beneficiaries of peak shaving, the load side, while enjoying clean energy, also needs to bear the responsibility of peak shaving and share part of the peak-shaving cost. In this regard, this paper proposes a peak-shaving cost allocation mechanism considering load-side participation. Firstly, the paper used the marginal contribution theory to establish the peak-shaving value evaluation model of the power and load. Then, based on the waveform similarity theory, the paper sets two indicators 'Fluctuation Trend Similarity' and 'Waveform Amplitude Difference' to evaluate each load's renewable energy consumption responsibility. Finally, the peak-shaving cost allocation rules on the power source side and the load side are obtained. The example shows that the proposed allocation mechanism can initially realize the uniform distribution of power and load in peak-shaving cost. Further more, the method can promote the fairness of peak-shaving market and guide users to reasonably participate in peak-shaving market.